Patient satisfaction across surgical units in tertiary care hospitals (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Patient satisfaction is the most primary thing during surgeries in tertiary care hospitals. Based onthe expectations of the patients, evolutions of the hospitals take place. In every health careinstitution, patient-level satisfaction assessment has become more important in terms ofenhancing quality as well as maintaining the sustainability of the hospitals. In this article, we willdiscuss patient satisfaction in tertiary care hospitals across surgical units. The surgical unit is oneof the important parts of the hospitals where patients receive special treatment and medicationsand recover through the surgical procedure. Patents are sent to the surgical units in critical caseswhere they need quality of care and protection. Satisfaction among the patients in the surgicalunits is most important for the recovery of the patients.